2020
DOI: 10.3390/su12104167
|View full text |Cite
|
Sign up to set email alerts
|

Natural Light Influence on Intellectual Performance. A Case Study on University Students

Abstract: Natural light in interior spaces has many advantages: the most obvious is energy savings, but also many long term physical and mental health benefits. Published research demonstrates the positive effects of natural light, especially in spaces used in long term periods, such as offices, houses, hospital rooms, etc. However, how would the deprivation of natural light affect users in spaces of more occasional use, such as lecture theatres, surgery rooms, courtrooms…? The present research consists in a case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A number of studies have found that students' academic performance in combined light environments is significantly higher than that of students in fully artificial lighting. [31][32][33] Therefore, the combined light environment was incorporated into the experiments in this study. On the other hand, in previous light environment experiments for the study of human physiological indices, there were few comprehensive comparative analyses of various physiological indicators, which made it impossible to macroscopically analyze the characteristics of human perception of the environment.…”
Section: Research Objectivesmentioning
confidence: 99%
“…A number of studies have found that students' academic performance in combined light environments is significantly higher than that of students in fully artificial lighting. [31][32][33] Therefore, the combined light environment was incorporated into the experiments in this study. On the other hand, in previous light environment experiments for the study of human physiological indices, there were few comprehensive comparative analyses of various physiological indicators, which made it impossible to macroscopically analyze the characteristics of human perception of the environment.…”
Section: Research Objectivesmentioning
confidence: 99%
“…managing hospital building envelopes (Porras Álvarez, 2020; Balali and Valipour, 2021; Jain et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, efficient energy management initiatives in hospitals can contribute to the achievement of SDG 7. Several elements are essential for the rational and efficient use of energy in hospitals: energy consumption management (Acampa et al , 2020; Blass et al , 2017; Ryan-Fogarty et al , 2016); managing use of green technologies (Franco et al , 2017; Khahro et al , 2021); and managing hospital building envelopes (Porras Álvarez, 2020; Balali and Valipour, 2021; Jain et al , 2021). …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Being able to work in natural light improves people's performance, as well as mood, and contributes to a better quality of life [17][18][19]. Many studies have focused on office buildings, but few have shown results for residential buildings, where-in the context of the pandemic-the number of hours spent in the home has increased due to teleworking and online classes [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%